2013
DOI: 10.1161/strokeaha.113.002794
|View full text |Cite
|
Sign up to set email alerts
|

THRIVE Score Predicts Ischemic Stroke Outcomes and Thrombolytic Hemorrhage Risk in VISTA

Abstract: Background and Purpose-In previous studies, the Totaled Health Risks in Vascular Events (THRIVE) score has shown broad utility, allowing prediction of clinical outcome, death, and risk of hemorrhage after tissue-type plasminogen activator (tPA) treatment, irrespective of the type of acute stroke therapy applied to the patient. Methods-We used data from the Virtual International Stroke Trials Archive to further validate the THRIVE score in a large cohort of patients receiving tPA or no acute treatment, to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 15 publications
4
105
4
2
Order By: Relevance
“…At least 7 such risk prediction scores have been proposed (Table 3). 9,[24][25][26][27][28][29] Validation studies comparing these scores in different populations of alteplasetreated patients have shown similar predictive values for the various scores (Table 3). [30][31][32][33][34][35][36][37] Although these scores generally are effective at estimating the incremental sICH risk facing individual patients, the upper range of absolute sICH risk predicted by the scores does not justify withholding thrombolytic therapy.…”
Section: Strokementioning
confidence: 92%
“…At least 7 such risk prediction scores have been proposed (Table 3). 9,[24][25][26][27][28][29] Validation studies comparing these scores in different populations of alteplasetreated patients have shown similar predictive values for the various scores (Table 3). [30][31][32][33][34][35][36][37] Although these scores generally are effective at estimating the incremental sICH risk facing individual patients, the upper range of absolute sICH risk predicted by the scores does not justify withholding thrombolytic therapy.…”
Section: Strokementioning
confidence: 92%
“…1 Various pretreatment clinical and imaging factors have been associated with hemorrhagic transformation after reperfusion treatment, including age, severity of pretreatment neurologic deficit, ischemic lesion volume, elevated blood pressure, serum glucose level, history of diabetes, and absence of collateral flow. [2][3][4][5] However, most available data on ICH following recanalization therapy in acute ischemic stroke are from studies of intravenous and intra-arterial pharmacologic fibrinolysis and little is known about the clinical and procedural factors contributing to ICH occurrence after mechanical neurothrombectomy. 6,7 The clinical impact of different ICH subtypes has also been incompletely studied.…”
mentioning
confidence: 99%
“…THRIVE and NIHSS were fairly accurate to predict worse functional outcome at hospital discharge. In previous studies THRIVE was shown to be a good predictor of clinical outcome, hemorrhagic transformation, and outcome after endovascular 10 and intravenous stroke treatment 11,12 . This score has been previously tested in North American, European, and Asian populations; however, to the best of our knowledge, this was the first study to evaluate this score in a South American population.…”
Section: Discussionmentioning
confidence: 92%